A Study on Teacher Leadership: A Systematic Review: Exploring Aims, Attributes, and Future Growth of Teacher Leadership (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This review is designed to initially allow readers to learn about teacher leadership and the different aims and types of teacher leadership. The analysis then shifts to national and international methods and frameworks for teacher leadership. The analysis then identifies the attributes and competences of good teacher leadership, the criteria for progress and suggestions for future growth, as teacher leadership needs to be cultivated and encouraged.